Effects of Educational Productivity on Career Aspiration Among United States High School Students - Wang, Jianjun; Ma, Xin (Alberta Journal of Educational Research, 2001)
The purpose of this study was to examine the effects of mathematics-related educational productivity on student career aspiration. We developed a structural model describing the relationship between educational productivity and career aspiration based on Walberg's (1981, 1992) theory of educational productivity. Using data from the Longitudinal Study of American Youth (LSAY), we identified eight mathematics-related factors of educational productivity descriptive of educational outcome, motivation, instructional characteristics, and psychological environment. Statistical results of the structural model supported Walberg's theory of educational productivity from the perspective of student career aspiration (as the educational outcome) in the context of mathematics education. Suggestions were made to enhance student career aspiration and improve the quality of mathematics education.